2020
DOI: 10.5888/pcd17.200277
|View full text |Cite
|
Sign up to set email alerts
|

The Arkansas Minority Barber and Beauty Shop Health Initiative: Meeting People Where They Are

Abstract: What is already known on this topic? Chronic diseases disproportionately affect racial/ethnic minority communities. Barber and beauty shops are recognized as viable locations to promote health and screen for chronic diseases. What is added by this report? This report describes screening for chronic health conditions at a barber and beauty shop-based screening program, the effect of a health education promotion campaign, and how medical referrals and participant follow-up can be integrated into screening initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 13 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The work from Smith and colleagues in Arkansas examines the benefits of using trusted community spaces such as barber and beauty shops for screening for chronic health conditions including blood pressure monitoring. Their findings indicate that community-based settings are effective in increasing knowledge of CVD-related risk factors and access to health promotion resources to reach minority populations ( 33 ).…”
Section: Using Community-based Approaches To Decrease Cvd Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…The work from Smith and colleagues in Arkansas examines the benefits of using trusted community spaces such as barber and beauty shops for screening for chronic health conditions including blood pressure monitoring. Their findings indicate that community-based settings are effective in increasing knowledge of CVD-related risk factors and access to health promotion resources to reach minority populations ( 33 ).…”
Section: Using Community-based Approaches To Decrease Cvd Riskmentioning
confidence: 99%
“…For example, Long and colleagues evaluated 3-year sodium reduction initiatives in 3 community meal programs in Arkansas (31). Jordan and colleagues demonstrated the differential effects of sodium reduction strategies in food service settings by tailoring community-level approaches based on a community's available resources, stage of readiness, and food service staff's level of engagement (32). These studies show the effectiveness and sustainability of the implementation of sodium reduction interventions in reducing CVD in communities experiencing food insecurity, low incomes, and high risk for hypertension (31,32).…”
Section: Using Community-based Approaches To Decrease Cvd Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Barbershops are considered important cultural venues with convenient community locations for addressing health and social issues that affect the Black community ( 21 ). The contribution by Smith et al ( 22 ) demonstrated the effectiveness of the Arkansas Minority Barber and Beauty Shop Health Initiative in improving CVD health outcomes of minority populations in the state through health screenings, health education, and disease management. This article describes chronic health conditions that presented during screening at a barber shop or beauty salon and the impact of a health education promotion campaign at this location.…”
Section: Objective and Themes Of The Collectionmentioning
confidence: 99%
“…In the United States, barbershops and beauty salons, for example, have been used as sites of health intervention to reach African American communities. Barbershops are considered important cultural venues with convenient community locations for addressing health and social issues that affect the Black community (21). The contribution by Smith et al (22) demonstrated the effectiveness of the Arkansas Minority Barber and Beauty Shop Health Initiative in improving CVD health outcomes of minority populations in the state through health screenings, health education, and disease management.…”
Section: Objective and Themes Of The Collectionmentioning
confidence: 99%